IMPLEMENTASI PRINSIP GOOD GOVERNANCE DALAM SISTEM PENGELOLAAN KEUANGAN DAERAH DI INDONESIA - Muhamad Pazri (Program Magister Hukum Universitas Lambung Mangkurat, 2016)
The purpose of this thesis is to determine and assess the implementation of Principle To recognize the importance of Good Governance in Financial Management System in Indonesia. To know Is General Principles of Local Financial management of the Implementation of Regional Finance can mewujukan Good Governance and How to Achieve Fiscal Management Principles for Being a Good Governance. Research in the writing of this law is to use the method of normative legal writing with properties that provide exposure deskrepsi study or overview of the implementation of Principles of Good Governance in Financial Management System In Indonesia and find How to Achieve Financial Management To Become Principles of Good Governance .. The law Primary use is legal action that the Minister of Home Affairs Number 21 Year 2011 concerning the Second Amendment of the Regulation of the Minister of Home Affairs Number 13 Year 2006 on guidelines for financial management, and secondary legal materials in the form of books and literature. After all the ingredients of the literature and research material collected then the materials are then processed and analyzed.According to this thesis and research results show that: First, the minimal prerequisites for achieving good governance is transparency, accountability, participation, legal empowerment, effectiveness and efficiency, and fairness. Second, implementation has Good Governance in Local Financial Management of renewal has always done.